Implementation of a Theoretical Approach for Electromagnetic Interaction - Sorongane , Elie W'ishe (New Trends in Physical Science Research Vol. 6, 2022)
With the exception of the electromagnetic interaction, which also includes repulsion events, all four fundamental interactions describe attraction phenomena. If the matter that makes up our Universe obeys the same physical laws, the four fundamental interactions should all exhibit the same behavior: attraction or repulsion. To characterize the electromagnetic interaction, a new approach termed the binding cord approach was developed in this paper. Electromagnetic repulsion will be described as a result of attraction in this new method. The binding cord approach will allow us to explain the stability and instability of particles only by knowing their respective charges and spins.